2015
DOI: 10.1111/1440-1681.12389
|View full text |Cite
|
Sign up to set email alerts
|

67‐kDa Laminin receptor contributes to hypoxia‐induced migration and invasion of trophoblast‐like cells by mediating matrix metalloproteinase‐9

Abstract: Insufficient trophoblast invasion often occurs in patients experiencing preeclampsia. The 67-kDa laminin receptor (LR1) is a multifunctional protein that binds to laminin and interacts with the extracellular matrix. We recently demonstrated that LR1 is implicated in trophoblast migration and invasion. However, whether LR1 is involved in hypoxia-mediated trophoblastic invasion remains unclear and requires further investigation. This study demonstrates that two trophoblast-like cell lines (JEG3 and BeWo cells) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…In addition, infection with human cytomegalovirus has been confirmed to inhibit extravillous cytotrophoblast migration and invasion through the dysregulation of CXCR4/CXCL12 signaling throughout early pregnancy ( 32 ). Consistent with several previous studies ( 6 , 33 , 34 ), the present study found that the migration and invasion of trophoblast cells were enhanced following exposure to 3% O 2 . Therefore, it was hypothesized that the expression of CXCR4 in trophoblasts depends on physiological hypoxia in early pregnancy.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, infection with human cytomegalovirus has been confirmed to inhibit extravillous cytotrophoblast migration and invasion through the dysregulation of CXCR4/CXCL12 signaling throughout early pregnancy ( 32 ). Consistent with several previous studies ( 6 , 33 , 34 ), the present study found that the migration and invasion of trophoblast cells were enhanced following exposure to 3% O 2 . Therefore, it was hypothesized that the expression of CXCR4 in trophoblasts depends on physiological hypoxia in early pregnancy.…”
Section: Discussionsupporting
confidence: 93%
“…26 Published studies have established the significance of BM proteins in placentation and embryogenesis in murine BM-proteins ablated models, 23 human placental tissue, 25,48,49 and cytotrophoblast invasion in vitro. 25,50,51 However, none of the studies to date have directly determined the impact of The MMP2 expressions for HMW-pECM was lower than that of complete pECM with no significant differences. LMW-pECM did not have a significant impact on the MMP2 expression (n 5 3).…”
Section: Discussionmentioning
confidence: 97%
“…Remarkably, some important extracellular factors, such as TGF-β, FGF and Wnt, participate in the regulatory network by inducing EMT and/or the expression of MMPs [ 23 27 , 29 , 40 , 41 ]. The mechanisms of hypoxia in this regulatory network are similar to those of extracellular factors, as shown in Figure 1 [ 28 , 29 , 42 , 43 ].…”
Section: The Mechanisms Underlying Emt and Their Role In Metastasismentioning
confidence: 99%